Предмет: Алгебра,
автор: Lskdekdjfj
(x-1)^2+(x+2)^2=2(1-x)(x-2) решите
Ответы
Автор ответа:
0
x^2+ 1+x^2+4= 2* x+2x
2x^2+5 = 2*3x
2x^2-6x+5=0
D= b^2-4ac= 36-4*2*5= -4
Или ты сделала ошибку в условие задания или так должно быть, дискриминант не может быть "-"
2x^2+5 = 2*3x
2x^2-6x+5=0
D= b^2-4ac= 36-4*2*5= -4
Или ты сделала ошибку в условие задания или так должно быть, дискриминант не может быть "-"
Похожие вопросы
Предмет: Математика,
автор: kolapinleonid
Предмет: Алгебра,
автор: hello9255
Предмет: Литература,
автор: lizaburtseva2009
Предмет: Физика,
автор: Лизонькааааа
Предмет: Химия,
автор: Slava988